Simulation of conjugate heat transfer between fluid-saturated porous media and solid wall - Chen, Sheng (Elsevier, 2018)
Conjugate heat transfer between fluid-saturated porous media and solid walls is an important issue in many disciplines. For traditional numerical techniques, it is still a great challenge to treat conjugate problems, especially with complicated interfaces. In the present work, a new numerical approach, based on the lattice Boltzmann (LB) method, is proposed to address such challenge. In the present approach no explicit special treatment on coupled interfaces between fluid-saturated porous media and solid walls is required. Moreover, no additional source term, which exists in the available LB models, is required. It can guarantee that the simplicity, accuracy and stability of the present model are better than those models. The accuracy and reliability of the present approach are validated by three nontrivial benchmark tests. The excellent agreement with previous published data demonstrates its feasibility and simplicity for modelling conjugate heat transfer with complicated interfaces between fluid-saturated porous media and solid walls. The present work takes a single-relaxation-time model for example to address conjugate heat transfer problems and its multiple-relaxation-time counterpart can be established straightforwardly in the same way.